2011
DOI: 10.1007/s11164-011-0243-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of formic and acetic acids from phenol by hydrothermal oxidation

Abstract: Hydrothermal technology is a core environmental-protection technique which can be used for waste water treatment and biomass conversion. In this paper a novel idea, alkaline hydrothermal oxidation, is proposed for producing formic and acetic acids from wastewater containing phenolic compounds. The effects of the most important conditions-reaction temperature, reaction time, oxygen supply, and type of alkaline catalyst-on yields of formic and acetic acids were investigated. The results indicated that the optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In addition, it seems that KOH is more effective than NaOH at promoting the production of carboxylic acids, and a similar result was also observed in our previous research. 8,31 Since the radius of K + is larger than that of Na + , it is proposed that KOH has a greater alkalinity, as well as a greater tendency than NaOH to react with the H in the OH groups of catechol to form o-quinone. Consequently, studies with KOH were conducted to optimize the production of C4-DCAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it seems that KOH is more effective than NaOH at promoting the production of carboxylic acids, and a similar result was also observed in our previous research. 8,31 Since the radius of K + is larger than that of Na + , it is proposed that KOH has a greater alkalinity, as well as a greater tendency than NaOH to react with the H in the OH groups of catechol to form o-quinone. Consequently, studies with KOH were conducted to optimize the production of C4-DCAs.…”
Section: Resultsmentioning
confidence: 99%
“…8 Since a lower H 2 O 2 supply is helpful to easily get the initial oxidation products, 9 a H 2 O 2 supply of 20−60% (H 2 O 2 concentration varies from approximately 0.65 to 1.95 mol/L) was selected in this study to produce C4-DCAs with larger molecular weights. As shown in Figure 5a, the yield of total C4-DCAs increased with the increase of H 2 O 2 supply, reached a maximum of 31.4% with 50% H 2 O 2 supply, and then decreased sharply with the H 2 O 2 supply increased to 60%.…”
Section: Optimization Of Reaction Condition For Gettingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is known that the constant ionization (k w ) of high temperature water is the maximum at near 300 °C at saturated vapor pressure. 35 The highest yield of lactic acid obtained at 300 °C may be related to the fact that the maximum ion product (k w ) of high temperature water occurs at about 300 °C. However, the yield of lactic acid further decreased with increasing reaction time from 1 to 5 min at 325 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, fairly high-purity fumaric acid is used in this study. Recently, many works have demonstrated that lignin models could also be oxidized into fumaric acid under hydrothermal conditions [26][27][28][29][30]. As a building block, fumaric acid has been widely studied [31].…”
Section: Introductionmentioning
confidence: 99%